PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO DAN SIZE TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Marzuki, Marzuki (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
The objective of this study is to examine the effect of ROE, DER, and firm size on stock prices of the manufacturing companies listed on the Indonesia Stock Exchange (IDX). The data used in this study were panel data sourced from the combination of cross section data and time series data. This research used purposive sampling method with the sample consisted of 86 manufacturing companies listed on IDX in 2017. Data were analyzed using multiple linear regression. The results showed that ROE and firm size had a positive and significant influence on stock price. However, DER did not have a significant influence on stock price. Keywords : ROE, DER, company size, stock price